1999
DOI: 10.1520/gtj11314j
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Interface Stresses During Pullout Tests on Geogrid Strip Reinforcement

Abstract: For a strip geogrid reinforcement, pullout resistance per unit width is known to increase with decreasing specimen width at low applied normal stresses. This phenomenon can be explained by a conceptualized model for a pullout interaction mechanism consisting of combined 2-D and 3-D interaction mechanisms, and the results obtained from laboratory pullout tests can be extended to the field. In this paper, a series of pullout tests on stiff extruded geogrid specimens embedded in dense sandy gravel was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…3. One of the settlement monitoring purposes is predicating the final settlement by the monitoring data [4,5] . The major predication method of more experienced is hyperbolic curve method and settlement rate method.…”
Section: Monitoring Analysis Of Section Dk664+160mentioning
confidence: 99%
“…3. One of the settlement monitoring purposes is predicating the final settlement by the monitoring data [4,5] . The major predication method of more experienced is hyperbolic curve method and settlement rate method.…”
Section: Monitoring Analysis Of Section Dk664+160mentioning
confidence: 99%
“…He found that the strength improved several times when there existed fiber materials in the earth. At present, there have many reports about the interface mechanics characteristics of the coarse-grained soils [2][3][4], but the reports about these characteristics of reinforced earth under one-way shearing force are less [5][6], not to mention the dynamic characteristics. In this paper, we have taken the one-way shearing test of coarse-graine soils and reinforced earth.…”
Section: Introductionmentioning
confidence: 99%